Wybrane aspekty sytuacji zawodowej a typ zawodu = Selected aspects of professional situation and type of a job - Zdaniewicz, Magdalena; Krasińska, Beata (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The article focuses on the selected work aspects and shows the reflections of an employee and their job. Nowadays there are all different kinds of job aspects. When looking at your job, one can distinguish several aspects such as: economical, physiological, psychological, intellectual or social ones. For an employee, apart from the aspects mentioned above, the important one is the aim. Seeing your job as a way to make money and keep your financial situation in a good condition served the authors as a basis for their research on selected job aspects.
Keywords: praca; sytuacja zawodowa; pracownik; zawód